Asset co-movements: Features and challenges - Nikolaj Gospodinov (Federal Reserve Bank of Atlanta, 2017)
This paper documents and characterizes the time-varying structure of U.S. and international asset co-movements. Although some of the time variation could be genuine, the sampling uncertainty and time series properties of the series can distort significantly the underlying signal dynamics. We discuss examples that illustrate the pitfalls from drawing conclusions from local trends of asset prices. On a more constructive side, we find that the U.S. main asset classes and major international stock indices share a factor that is closely related to the business cycle. At even lower frequency, the common asset co-movement appears to be driven by demographic trends.
Keywords: G13; G14; G17; 330; cross-asset; within-asset and international asset co-movements; rolling correlation; time-variability; persistence; higher moments; risk factors; sampling frequency